(untitled) (Proceedings of the International Conference on Food, Nutrition, Health and Lifestyle, 2024)
: In Indonesia, anemia and stunting are still commonly found among girls adolescent, even though this can happen to the same person and the same time. So intervention is needed to overcome this. The study aims to assess the effect of school-based integrated interventions on the coexistence of anemia and stunting. The quasi-experimental design was used, involving 342 female students from 4 schools, namely two intervention schools (the Ministry of Education, Culture, Research, and Technology) and two comparison schools (the Ministry of Religion). The intervention group received nutrition-health education from trained teachers (4 weeks) and implementation of an integrated adolescent girls Posyandu (4 months) that establish previously to monitor growth, nutritional status, and multi-micro-nutrient supplementation by health center staff. While the comparison group only received nutrition-health education from trained teachers for four weeks. Height measurement adjusted for the age to determine the HAZ-score (stunted: HAZ-Score value is <-2 SD). Measurements of hemoglobin levels using a blood photo meter Hemocue to determine anemia (Hb <12 g/dl). Data were analyzed using the chi-square test and Mc Nemar test. Before the intervention, there was no significant difference (p=0.527) in the coexistence prevalence of anemia and stunting between the intervention group (5.7%) and the comparison group (6.3%). However, after the intervention, there was a significant difference in the prevalence of the coexistence of anemia and stunting between the two groups (p = 0.016). In the intervention group, the coexistence of anemia and stunting was decrease by 1.2%, while in the comparison group increased almost two times (12.5%). Therefore, school-based integrated interventions for female adolescent are crucial as a form of investment to break the chain of malnutrition.